GENDER INEQUALITY WITHIN A FAMILY: THE REPRESENTATION OF WOMEN’S NOVEL IN SOCIAL MEDIA - Fitriani, Laily; Muassomah, Muassomah (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2021)
A topic about women is always interesting to discuss, including their works, such as a novel. Her life journey has been portrayed in a novel in detail. This paper aims to describe the representation of a women's novel in social media, the factors leading to it, and the values within. It employed a qualitative descriptive method with a feminist literary approach that examined the text from the women's side as a reader. Data were taken from a novel published online in social media and then printed. It was Elena. This study showed that women's novels in social media tend to experience marginalization/discrimination, stereotype/negative labeling, subordination, and excessive burden for women. The dominating cultural construction, patriarchy ideology, and familial ideology are the influencing factors. Women's novel also contains messages about religious values, education values, and the values of patience and endurance. It suggested that further research compared it with other novels published in social media or other media to provide a more comprehensive and varied description.